1994
DOI: 10.1128/jb.176.5.1287-1296.1994
|View full text |Cite
|
Sign up to set email alerts
|

A rationale for autoinduction of a transcriptional activator: ethanolamine ammonia-lyase (EutBC) and the operon activator (EutR) compete for adenosyl-cobalamin in Salmonella typhimurium

Abstract: The ethanolamine utilization (eut) operon of Salmonella typhimurium is controlled by a positive regulatory protein (EutR) which stimulates eut operon expression in response to the simultaneous presence of two effectors, ethanolamine and adenosyl-cobalamin (Ado-B12). Ado-B12 is a cofactor for ethanolamine ammonialyase (lyase), the first enzyme in the ethanolamine-degradative pathway. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 24 publications
1
52
0
Order By: Relevance
“…The transcriptional regulator PocR is necessary for Pdu MCP formation (19,(21)(22)(23). We confirmed that the analogous transcriptional regulator EutR is necessary for Eut MCP formation by two methods: first using a fluorescent reporter of P eut transcription (24,25) and then using a fluorescent reporter of encapsulation in the Eut or Pdu MCP (8). We observed activation of the P eut promoter by 30 mM ethanolamine and 150 nM vitamin B 12 as indicated by increased GFP fluorescence in an S. enterica strain containing the P eutgfpmut2 transcriptional reporter as compared with a control culture to which no ethanolamine and vitamin B 12 were added.…”
Section: S Enterica ⌬Eutr::frt Does Not Form Eut Mcps But Can Form Pdusupporting
confidence: 63%
“…The transcriptional regulator PocR is necessary for Pdu MCP formation (19,(21)(22)(23). We confirmed that the analogous transcriptional regulator EutR is necessary for Eut MCP formation by two methods: first using a fluorescent reporter of P eut transcription (24,25) and then using a fluorescent reporter of encapsulation in the Eut or Pdu MCP (8). We observed activation of the P eut promoter by 30 mM ethanolamine and 150 nM vitamin B 12 as indicated by increased GFP fluorescence in an S. enterica strain containing the P eutgfpmut2 transcriptional reporter as compared with a control culture to which no ethanolamine and vitamin B 12 were added.…”
Section: S Enterica ⌬Eutr::frt Does Not Form Eut Mcps But Can Form Pdusupporting
confidence: 63%
“…Interestingly, evidence from R. capsulatus suggests that shown to perform sensory functions, in addition to catalytic functions (Beinert & Kiley, 1999;Christie & Briggs, 2001;Gilles-Gonzalez, 2001;Braatch et al, 2002;Masuda & Bauer, 2002;. Two groups hypothesized that corrinoids might regulate activities of transcription factors (Roof & Roth, 1992;Sheppard & Roth, 1994;Cervantes & Murillo, 2002). The latter report is especially relevant because it considers a possibility that DNA-binding activity of M. xanthus ORF10 (CarA) might be corrinoiddependent.…”
Section: Discussionmentioning
confidence: 99%
“…In this bacterium, the availability of cobalamin may be noticed by a riboswitch identified in the untranslated region of the eut operon (Fox et al, 2009). In Salmonella enterica, the eut gene cluster (and also the cob/cbi cluster) are regulated positively by EutR, which is induced by the presence of ethanolamine and cobalamin (Sheppard & Roth, 1994).…”
Section: Staib and T M Fuchsmentioning
confidence: 99%